(untitled) (Docentes 2.0 Journal, 2024)
Today, technology has revolutionized both teaching and learning. Therefore, integrating technological tools into education has generated new opportunities and challenges. The objective was to examine the implementation of technology in the teaching-learning context by analyzing benefits, obstacles, and effective strategies to maximize its impact. The research was based on the systematic method, constructivist paradigm, and qualitative approach, with a biographical narrative design and exploratory documentary type. The study focused on the university educational environment, evaluating the impact of technology in this context. The sample included various bibliographic sources reviewed to obtain a comprehensive view of the importance of technology in education and the role of the teacher in its implementation. Meta-analysis techniques were used to collect and analyze the information. The results showed that technology was adapted to students’ individual needs, promoted global collaboration, and enriched the educational process. However, obstacles such as the digital divide and the need to guarantee online security and privacy were identified. The conclusions highlighted the importance of ongoing teacher training and assessment to make the most of the digital transformation in education.